Cortical Bone Material Strength Index and Bone Microarchitecture in Postmenopausal Women With Atypical Femoral Fractures. (5th November 2018) - Popp, Kristin L; Caksa, Signe; Martinez‐Betancourt, Adriana; Yuan, Amy; Tsai, Joy; Yu, Elaine W; Bouxsein, Mary L
ABSTRACT: Atypical femoral fractures are rare fractures that occur in the subtrochanteric or diaphyseal region of the femur with minimal or no trauma. Though the association of atypical femoral fractures (AFFs) and bisphosphonate (BP) use is a growing concern in the management of osteoporosis, currently there is little knowledge about which patients may be at risk for an atypical femoral fracture. Given that these fractures initiate in the femoral cortex, we aimed to determine whether cortical bone tissue properties (bone material strength index; BMSi), as measured by in vivo impact microindentation, are altered in atypical fracture patients. We also aimed to identify factors associated with the BMSi measurements. We enrolled postmenopausal women with recent AFFs ( n = 15) or hip fractures (Hip Fxs; n = 20), long‐term (>5 years) BP users ( n = 30), and treatment naïve controls ( n = 88). We measured total hip and femoral neck BMD by DXA, cortical bone microstructure at the distal tibia by HR‐pQCT, and BMSi at the midtibia by impact microindentation. BMSi values were similar in all groups, with no effects of long‐term BP use or lower values in patients with AFFs or Hip Fxs, even after multivariable adjustment. BMSi measurements were independent of age, femoral BMD, duration of BP treatment, vitamin D level, and cortical bone microstructure, including cortical porosity and cortical tissue mineral density. In conclusion, impact microindentation values are not negatively affected by long‐term BP use and do not appear to discriminate individuals who suffer AFFs. Thus, our results do not support clinical use of impact microindentation to identify those at risk for AFFs. This remains to be verified in larger studies. © 2018 American Society for Bone and Mineral Research.